2005
DOI: 10.1007/s11894-005-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux and gastric emptying, revisited

Abstract: Total gastric emptying is delayed in 10% to 33% of adult patients with gastroesophageal reflux disease (GERD), but a strong correlation between duration of gastric emptying and severity of acid reflux or esophagitis has never been proved. Previous studies reported that patients with GERD might have exaggerated postprandial fundus relaxation with retention of food and triggering of transient lower esophageal sphincter relaxations (TLESRs). There is a positive correlation between postprandial fundus relaxation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 58 publications
3
49
1
2
Order By: Relevance
“…Delayed gastric emptying occurs frequently among patients with acid reflux (3,31), and treatment with prokinetic agents, which are agonists of the 5-hydroxytryptamine 4 (5-HT 4 ) receptor, partially improves symptoms in patients with GERD (16,39). Thus it was concluded that gastric dysmotility is also a factor involved in acid reflux into the esophagus (3,10,29,31). However, the reasons for gastric dysmotility remain unclear.…”
mentioning
confidence: 99%
“…Delayed gastric emptying occurs frequently among patients with acid reflux (3,31), and treatment with prokinetic agents, which are agonists of the 5-hydroxytryptamine 4 (5-HT 4 ) receptor, partially improves symptoms in patients with GERD (16,39). Thus it was concluded that gastric dysmotility is also a factor involved in acid reflux into the esophagus (3,10,29,31). However, the reasons for gastric dysmotility remain unclear.…”
mentioning
confidence: 99%
“…29 Few reports thus far have analyzed the relationship between gastric emptying and non-acid GERD using pH/MII, although a close relationship between DGE and GERD in both adults and children has been reported from a considerable number of studies. Emerenziani et al 30 reported a significant relationship between reflux acidity and gastric emptying; namely, the slower the emptying, the higher the pH of the refluxate. To the best of our knowledge, Kawahara et al 12,13 are the only investigators who reported the relationship between DGE and GERD in NI patients by utilizing both pH/MII and 13 C-ABT analyses; they concluded that there was no significant relationships between DGE and GERD.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that food retention in the stomach may work as a prolonged potent buffer against gastric acid, and this effect could lead to the generation of a less damaging, weakly acidic refluxate. Emerenziani et al investigated the relationships between the emptying of the total, proximal, and subcardial stomach and GER using scintigraphy and combined MII-pH monitoring in adults with asymptomatic and symptomatic GERD [26]. Their findings suggest that the rate of gastric emptying does not affect the total number of reflux events, but does determine refluxate acidity, including the total proportion of postprandial acid, as well as the amount of weakly acid and non-acid reflux: the slower the emptying, the higher the pH of the refluxate.…”
Section: Discussionmentioning
confidence: 99%